2000
DOI: 10.1159/000051951
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Ablation of Colorectal Liver Metastases: 1-Year Histological Patient Follow-Up

Abstract: Whilst up to 50% of patients with colorectal carcinoma will develop liver metastases, only 20% of those patients will be amenable to potentially curative liver resection. There is therefore great need for other effective therapies, and we report complete ablation of a colorectal liver metastasis using electrolysis, which was histologically confirmed at 1 year. The clinical impact of complete tumour ablation at 1 year means that a proportion of those patients currently deemed inoperable and therefore incurable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…From the present study and the reviewed literature it is apparent that electrolysis is a reliable, reproducible, and predictable method for the potentially curative treatment of unresectable liver tumors. Early reports on electrolysis in humans with liver metastases have shown complete ablation of metastases with no histological recurrence at 12 months following ablation [45]. This study has also demonstrated that concurrent intermittent hepatic ischemia significantly increases the efficacy of electrolysis in producing large volumes of hepatic necrosis.…”
Section: Figuresupporting
confidence: 60%
“…From the present study and the reviewed literature it is apparent that electrolysis is a reliable, reproducible, and predictable method for the potentially curative treatment of unresectable liver tumors. Early reports on electrolysis in humans with liver metastases have shown complete ablation of metastases with no histological recurrence at 12 months following ablation [45]. This study has also demonstrated that concurrent intermittent hepatic ischemia significantly increases the efficacy of electrolysis in producing large volumes of hepatic necrosis.…”
Section: Figuresupporting
confidence: 60%
“…It is probably due to a combination of cytotoxic chemical production, pH changes and membrane disruption, although ischaemia and other host factors may also play a role [13][14][15][16][17][18][19][20][21][22]24,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…It does not rely on thermal effects at low currents [3,[11][12][13][14][15] and has been shown to be safe, predictable and effective in a linear dose-related manner [16][17][18]. The use of small metallic electrodes makes electrolysis suitable for percutaneous use.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical studies have reported the ability of electrolysis to destroy tumor tissue in various organs such as the skin, liver, or breast. However, complete regression of a malignancy was rarely observed [Berry et al, 2000;Telló et al, 2007]. EChT-like, high-intensity focused ultrasound or RFA is not selective and will destroy normal cells as well as tumor cells.…”
Section: Electrochemical Treatment Of Cancermentioning
confidence: 99%